Realtime hybrid offline-online power loss analysis-based Simulink simulation - Sulistyowati, Riny; Prawidya, Ganesha Fikri; Sujono, Hari Agus (International Journal of Applied Power Engineering (IJAPE), 2023)
The power distribution system applied in Indonesia is the radial system. The system is considered to be the simplest and most economical. The bad or good distribution of electrical power can be observed from the quality of the distribution of power supplied. Voltage has to be monitored and kept constant. An analysis was conducted at Bendul Merisi Feeder which has 11 buses, to find the value of supplied power also the value of voltage drop of each bus. The Simulink method is used to simulate and analyze active and reactive power at each cluster. Based on the result of the simulation analysis, the average was obtained by adding up electrical power received every hour, then dividing by 10, the number of buses connected to the load. The smallest average of active power supplied to each bus happened at 09.00 a.m., i.e. 112137.94 VA. The biggest value of active power supplied to each bus happened at 1.00 p.m., i.e. 115129.05 VA. The total voltage drop that occurred in the distribution supply was 224 volts or 1.12% out of 20 kV supplied, indicating that the supply of voltage was according to the standardized rule implemented by PLN (State Electricity Company), i.e. the voltage drop should not exceed the maximum of 10%.